2021
DOI: 10.37001/emr-rs.v.2.n.22.2021.p.3-14
|View full text |Cite
|
Sign up to set email alerts
|

Tarefas De Visualização Em Exercícios De Geometria Espacial

Abstract: Apresenta-se, neste artigo, uma pesquisa de cunho qualitativo, cujo objetivo é analisar exercícios de livros didáticos de matemática que demandam habilidade de visualização espacial para sua resolução. Para tanto, foram investigadas várias ações (tarefas de visualização) apresentadas em artigos científicos nas áreas de Ensino e de Educação Matemática. Na pesquisa, foi proposta uma classificação das ações e utilizou-se dessa categorização como critérios de análise.  Os exercícios de Geometria Espacial analisado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 1 publication
0
9
0
2
Order By: Relevance
“…In quantitative and general terms, it is noteworthy that the prevalence of questions requiring SVS among those of SG in the years of ENEM application that we analyzed was 39.7%. This is considerably higher than the analogous proportion in the four textbooks analyzed by Mathias and Simas (2021), which ranged from 14.0% to 19.8%. This suggests that ENEM item (question) developers are more aligned with the role of SG in basic 6 / 11 education than textbooks, with regard to SVS (Brasil.…”
Section: Analysis Of Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…In quantitative and general terms, it is noteworthy that the prevalence of questions requiring SVS among those of SG in the years of ENEM application that we analyzed was 39.7%. This is considerably higher than the analogous proportion in the four textbooks analyzed by Mathias and Simas (2021), which ranged from 14.0% to 19.8%. This suggests that ENEM item (question) developers are more aligned with the role of SG in basic 6 / 11 education than textbooks, with regard to SVS (Brasil.…”
Section: Analysis Of Resultsmentioning
confidence: 57%
“…In this regard, when analyzing Brazilian high school mathematics textbooks, Mathias and Simas (2021) used the five actions present in tasks of interpretation of perspectives of three-dimensional objects (Gonzato et al, 2011) to categorize actions required in tasks that demanded SVS for their resolution, as shown in Table 2. We observed that SO was not explored in Mathias and Simas (2021), although it was mentioned in Gonzato et al (2011), since tasks that require this type of element are generally addressed in the early years of elementary school.…”
Section: Spatial Visualization Skillsmentioning
confidence: 68%
See 3 more Smart Citations